Placental Neutrophil Infiltration Associated with Tobacco Exposure but Not Development of Bronchopulmonary Dysplasia - David M. Box; Abhishek Makkar; Zhongxin Yu; Hala Chaaban; Henry H. Tran; Kathryn Y. Burge; Jeffrey V. Eckert (MDPI AG, 2022)
Objective: In utero inflammation is associated with bronchopulmonary dysplasia (BPD) in preterm infants. We hypothesized that maternal tobacco exposure (TE) might induce placental neutrophil infiltration, increasing the risk for BPD. Study design: We compared the composite outcome of BPD and death in a prospective pilot study of TE and no-TE mothers and their infants born <32 weeks. Placental neutrophil infiltration was approximated by neutrophil gelatinase-associated lipocalin (NGAL) ELISA, and total RNA expression was analyzed via NanoString© (Seattle, WA, USA). Result: Of 39 enrolled patients, 44% were classified as tobacco exposure. No significant difference was noted in the infant's composite outcome of BPD or death based on maternal tobacco exposure. NGAL was higher in placentas of TE vs. non-TE mothers (p < 0.05). Placental RNA analysis identified the upregulation of key inflammatory genes associated with maternal tobacco exposure. Conclusion: Tobacco exposure during pregnancy was associated with increased placental neutrophil markers and upregulated inflammatory gene expression. These findings were not associated with BPD.